Synthesis new Trifluoperazine Selective Liquid Electrodes Depending on Molecularly Imprinted Polymers Based on PVC Membrane for Determination of Trifluoperazine from Pharmaceutical Samples - Ahmed Mohsen Dhari (Journal of Global Pharma Technology, 2018)
Liquid electrodes of polymers imprinted with Trifluoperazine were synthesized based on Mechanics polymerization of precipitation. The molecularly imprinted polymer (MIP) and non-imprinted polymers (NIP) It was manufactured using (TFP) as a template. In polymerization process, 2-Hydroxy ethyl meth acrylate (2-HEMA) and 2-Vinyl Pyridine (2-VP) were used as monomers. Divinylbanzene (DVB) was used as cross-linkers and benzoyl peroxide (BPO) as an initiator. The molecularly imprinted membranes and the molecularly non-imprinted membranes were synthesized utilize DibutylSebacate (DBS) and Nitro benzene (NB) as plasticizers in PVC matrix. Detection limit and Slopes of the liquid electrodes are ranged at (3 × 10-6– 8 × 10-6) M and (21.83– 23.03) mV/decade, respectively. Response time was 60 seconds. The electrodes were filled with liquid of 10-1 M standard solution of drug and observed stable response for a pH ranged from 1.5 to 12 and with good selectivity for more than several types. The new synthesis electrodes were successfully used for the analyte estimated in preparation pharmaceutical sample without any time consuming pretreatment steps.Keywords: Molecularly imprinted electrodes; Trifluoperazine; Potentiometric method; (2-HEMA); (2-VP) monomers